2018
DOI: 10.1007/s40273-018-0640-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Relative Importance of Attributes of Metastatic Renal Cell Carcinoma Treatments to Patients and Physicians in the United States: A Discrete-Choice Experiment

Abstract: Patients and physicians indicated that PL3Y was the most important treatment attribute and was significantly more important than PFS. Importance rankings differed between physicians and patients and between all patients and those with advanced/metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Similar DCE studies in oncology that utilized online panels also reported study populations with relatively young mean ages (<55 years old). 42,43 We further explored this by comparing the RAISs between younger and older patients in our sample. Some differences in the importance ranking of attributes did change with respect to fatigue, rash, and cognitive problems, but the top two most important and two least important attributes remained the same (results not shown).…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…Similar DCE studies in oncology that utilized online panels also reported study populations with relatively young mean ages (<55 years old). 42,43 We further explored this by comparing the RAISs between younger and older patients in our sample. Some differences in the importance ranking of attributes did change with respect to fatigue, rash, and cognitive problems, but the top two most important and two least important attributes remained the same (results not shown).…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…Therefore, given the lower value attributed to SAEs, oncologists were willing to accept a slightly higher increase in SAE risk than patients in exchange for 1-month survival gain (4.2% oncologists and 3.0% patients). In contrast, Gonzalez et al showed that although efficacy was the most important attribute for both physicians and patients, the former gave greater importance to fatigue, skin reactions or other attributes such as co-payment (22). These results would be in line with those observed by Lawrence et al, in which the survival times judged sufficient to warrant treatment (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Each of the treatments is associated with different clinical outcomes, administration modes, treatment-related adverse events, and costs (22), so decisions about therapy involve tradeoffs between the possible benefits and harms (9). The European Medicines Agency has indicated that in order to improve the management of treatment toxicities, it is important to better understand the extent to which patients are willing to tolerate AEs and, therefore, the relative importance patients give them (23).…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies have explored the value that patients, providers, or both place on aspects of benefits and burdens of treatment, including progression-free survival (PFS), landmark overall survival (OS), or toxicities in lung cancer, 13–22 melanoma, 12 , 20 , 23 , 24 and renal cell carcinoma. 25–28 However, no study to date has been designed to elicit how patients and their physicians value a set of attributes with the unique profile of immuno-oncologic treatments, including how patients and physicians trade off increases in mean or median survival versus an increased chance of remission or durable survival or avoiding toxicities associated with cytotoxic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%